INTRAOPERATIVE CORRECTION OF BIO-OXIDATIVE SUPPORT OF HOMEOSTASIS IN PATIENTS WITH BREAST CANCER - Шульга, М.В. (World of Medicine and Biology, 2014)
Analysis of the effectiveness of improved perioperative intensive care revealed that intraoperative antioxidant protection of oxidative homeostasis in surgical interventions in the form of quadrantectomy of breast with lymph node dissection allows you to monitor and influence the mechanisms of glycolysis (increased activity of anaerobic oxidation and reduction in the Krebs cycle), while maintaining at the proper level concentrations of adenine nucleotides is possible only under the condition intraoperative antioxidant protection.
Keywords: intraoperative intensive therapy; oxidative homeostasis; breast cancer